New rapid test for prenatal detection of trisomy 21 (Down's syndrome): preliminary report. Issue 6841 (13th June 1992) - Bryndorf, T.; Christensen, B.; Philip, J.; Hansen, W.; Yokobata, K.; Bui, N.; Gaiser, C.
Abstract : OBJECTIVE–To devise and evaluate a rapid screening method for detecting trisomy 21 (Down's syndrome) in samples of uncultured amniotic fluid cells. DESIGN–Non-radioactive in situ hybridisation with HY128, a 500, 000 base pair yeast artificial chromosome probe specific for chromosome 21. Blinded study of 12 karyotypically normal amniotic fluid samples and eight samples trisomic for chromosome 21. SETTING–Cytogenetic and obstetric services at a tertiary referral centre, Copenhagen. MAIN OUTCOME MEASURES–Time necessary to complete the test. Proportion of cell nuclei containing two and three hybridisation signals in karyotypically normal and abnormal amniotic fluid samples. RESULTS–The test could be completed within three to four days after amniocentesis. In the normal samples a mean of 73% (range 61-82%) of the amniotic cell nuclei showed two hybridisation signals and 6% (0-18%) showed three signals. By contrast, among the trisomic samples 29% (19-38%) of the nuclei exhibited two signals and 48% (31-60%) showed three signals. CONCLUSION–The technique clearly distinguished between normal and trisomic samples. Prenatal diagnosis with in situ hybridisation with chromosome specific probes was fast and may make it possible to screen for selected, aneuploidies. However, the technique is still at a preliminary stage and needs further evaluation and refinement.